EFFECT OF USING LEAD RUBBER BEARING ON A STEEL ARCH BRIDGE - Kusumastuti, Dyah; Lim, E -; Asneindra, M; Mulyadi, Sandy (Jurnal Teknik Sipil, 2022)
A study was conducted to evaluate the application of Lead Rubber Bearing (LRB) on bridge structures. The length of steel arch bridge is 80 m, width of 10 m, and height of 19.6 m. The bridge is simply supported with two bearings on each support. Structural analysis reveals that the lateral force on the bearing is more than 400 tons (835 tons in longitudinal direction). The original designer"™s intention is to use pot bearings. However, the pot bearing was required to undergo some mechanical test to verify its properties prior to installation. Due to its size, this scheme is not applicable due to the limitations of the testing facility. Therefore, an alternative design was evaluated using LRB to reduce the reaction force, hence downsize the bearing size. The LRB used is of LRB 7500 characteristics, and the calculation refers to AASHTO Guide Specifications for Seismic Isolation Design (GSID), 4th edition 2014.The analysis shows that applying LRB on the bridge lengthened the structural period from 0.76 seconds to 1.67 seconds. It also increased the damping ratio from 5% to 43 %. With these significant changes in structural parameters, lateral forces due to earthquake loads on the bearing and foundation can be greatly reduced. The study found that replacing pot bearings with LRBs can reduce the lateral force to 80 tons, approximately one fifth from the previous design. Correspondingly, the internal forces of some major structural components of the bridge can be reduced due to the application of LRB.